General model of a transport-technological grain store route node for control systems programs (Computer systems and information technologies, 2021)
The paper concerns a problem to develop software for engineering control systems based upon standard industrial controllers and SCADA means at enterprises for grain storage and processing. The problem generalizing approaches to develop algorithms controlling equipment as a part of technological routes has been considered. A system to control transport-technological grain route at grain storage is the research object.  Control of transport-technological equipment at a route level is the research subject. Purpose is to develop general control model for nodes of a network of transport-technological grain storage routes to formalize tasks of software creation for industry specific engineering systems.Analysis, classification, and generalization of processing equipment have been carried out; approaches to implement functional structures of elevator routes have been studied. General model to control transport-technological grain storage route has been proposed in the form of a graph of states. Transitional conditions in the form of algebraic logic have been developed for this graph as well as algorithms to control certain mechanisms in terms of transitional states of the route.The control model developed in the form of graph involving transitional conditions and algorithms of transitional states has obtained its software implementation; moreover, it has been introduced in the context of industry specific engineering control systems at operating enterprises of grain storage and processing. The introduction results have demonstrated the model stability under the conditions of different enterprises engaged in grain storage and processing from the viewpoint of its implementation in the system software.The realized field experiments have demonstrated the system effectiveness, which allows to recommend it to solve the problems of software development for engineering control systems based upon standard industrial controllers and SCADA.
Keywords: transport-technological grain storage routes, general control model, graph of states, industrial controller, SCADA